Sleep Quality and Perceived Stress in Diverse Work Environments: The Role of Noise Exposure and Sociodemographic Factors - Afinwala, Abhishek S; Chauhan, Naresh T; Bodar, Kavita G; Gohil, Jigna D; Patel, Harshad M; Kosambiya, Jayendrakumar K (National Journal of Community Medicine, 2025)
Background: Sleep disturbance is the most detrimental non-auditory effect of noise exposure. Study aims to assess perceived stress and sleep quality across different occupational and noise exposure environments, and to identify sociodemographic and occupational predictors of poor sleep. Methodology: A cross-sectional study in Surat included 160 participants from three work environments based on noise exposure: New Civil Hospital Surat (30-50 dB), the urban field practice area (50-70 dB), and textile industries (>70 dB) using stratified, systematic, and simple random sampling methods, respectively. Univariate analysis using Chi-square and Kruskal-Wallis H tests identified associations, while binary logistic regression determined independent predictors. Results: Textile workers reported the highest poor sleep quality (88.9%). Significant differences in sleep quality (p=0.001), but not stress (p=0.650), were observed across groups. Poor sleep was significantly associated with education, occupation, socioeconomic class, and shift work. Logistic regression revealed age, postgraduate education, and higher socioeconomic status as independent predictors of poor sleep. Conclusion: Sleep quality is influenced by education, job type, socioeconomic class, and shift work, with poorer sleep in older, educated, and wealthier individuals. No significant association was found for perceived stress.